PENGARUH PEMBIAYAAN MURABAHAH, IJARAH DAN MUSYARAKAH TERHADAP PROFITABILITAS PADA BANK UMUM SYARIAH - Siti Zahrah; Dyarini (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to determine the effect of murabahah financing, ijarah financing, and musyarakah financing on profitability at Indonesian Islamic Banks. This research is quantitative, using secondary data sources obtained from Indonesian Islamic Commercial Banks for 2016 - 2022. The sampling method uses purposive sampling method , obtained a total sample of 6 Islamic Commercial Banks for 7 years, so that 38 annual reports were obtained. Methods of data analysis using descriptive analysis test, panel data regression test, classical assumption test, model feasibility test, using Eviews version 12. The results showed that murabahah financing had a positive and significant effect on profitability, ijarah financing had a negative and insignificant effect on profitability, and musyarakah financing has a negative and significant effect on profitability.